2006
DOI: 10.1167/iovs.05-0067
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Imaging Algorithm for Scanning Laser Polarimetry with Variable Corneal Compensation

Abstract: RNFL morphology may be better assessed with the presented ECC method than with standard VCC. ECC may be implemented in the current VCC systems by means of a software upgrade. It may enhance the clinical utility of the GDx VCC in glaucoma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 20 publications
6
85
4
Order By: Relevance
“…We have recently demonstrated how a control cohort with no suspicious findings of glaucoma can affect the diagnostic ability of SDOCT parameters in glaucoma compared with a control cohort which is likely to be misinterpreted as glaucoma. 16 Due to the same reason, AUCs of RNFL parameters reported in our study are also lower compared with the studies that have reported the same with SDOCT 7,10,29 and GDx ECC 5,12,13,30 separately.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…We have recently demonstrated how a control cohort with no suspicious findings of glaucoma can affect the diagnostic ability of SDOCT parameters in glaucoma compared with a control cohort which is likely to be misinterpreted as glaucoma. 16 Due to the same reason, AUCs of RNFL parameters reported in our study are also lower compared with the studies that have reported the same with SDOCT 7,10,29 and GDx ECC 5,12,13,30 separately.…”
Section: Discussioncontrasting
confidence: 46%
“…The general principles of SLP and the algorithm used for ECC have been described in detail previously. 3,5,12 The parameters generated on the printout and used in this study were temporal average (temporal 50 degree), superior average (superior 120 degree), nasal average (nasal 70 degree), inferior average (inferior 120 degree), TSNIT (temporal superior nasal inferior and temporal) average (over 360 degree), TSNIT SD, and nerve fiber indicator (NFI). TSNIT SD represents the SD of the values contained in the calculation circle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECC protocol introduces a predetermined birefringence bias to shift the measurement of the total retardation to a higher value region to remove noise and reduce atypical patterns. The amount of birefringence bias is then mathematically removed point by point from the total birefringence pattern of the image, to improve the signal and obtain a retardation pattern of the RNFL with the least noise (atypia) (Toth & Hollo 2005;Reus et al 2006;Sehi et al 2006). ABP in SLP scans is quantified by a support vector machine score called typical scan score (TSS) (Bagga et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…9 An analysis of the contribution of backscattered light from various depths to the total retardation map using spectral-domain OCT found that atypical retardation patterns in SLT are associated with deep penetration of the probing light beam into the strongly birefringent sclera. 12 To improve the accuracy, first the already-mentioned VCC, 13 then the software-based ECC 14 were introduced. It appears that GDx ECC performs better than VCC in the detection of glaucoma in early stages of disease.…”
mentioning
confidence: 99%